2008
DOI: 10.1111/j.1872-034x.2007.00304.x
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II and epidermal growth factor receptor cross‐talk mediated by a disintegrin and metalloprotease accelerates tumor cell proliferation of hepatocellular carcinoma cell lines

Abstract: These results suggest that AngII-EGFR cross-talk signaling mediated by ADAMs is involved in the proliferation and invasion activities of several HCC cell lines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 45 publications
1
32
0
Order By: Relevance
“…HB-EGF binds and activates intracellular signaling cascades downstream of EGFR, such as the AKT pathway, and thereby promotes the growth of normal and neoplastic cells (25,26). In our study, we found that the EGFR-AKT pathway was involved in the suppressive action of miR-126/ADAM9 in ESCC.…”
Section: Overexpression Of Mir-126 Suppresses Escc Cell Proliferationmentioning
confidence: 49%
See 1 more Smart Citation
“…HB-EGF binds and activates intracellular signaling cascades downstream of EGFR, such as the AKT pathway, and thereby promotes the growth of normal and neoplastic cells (25,26). In our study, we found that the EGFR-AKT pathway was involved in the suppressive action of miR-126/ADAM9 in ESCC.…”
Section: Overexpression Of Mir-126 Suppresses Escc Cell Proliferationmentioning
confidence: 49%
“…In addition, we investigated the downstream pathway and found that ADAM9 was critical for promoting cell proliferation in ESCC by targeting EGFR-AKT signaling. ADAM9 cleaved the pro-HB-EGF precursor to yield soluble HB-EGF, which binds to EGFR, thereby activating downstream signal transduction (26,41). The EGFR-AKT pathway is important for cell growth and migration (42,43).…”
Section: Discussionmentioning
confidence: 99%
“…Although they all overexpress EGFR, the expression level is greater in PC-9 than in either of the wild type cell lines, A549 or H460 (Okabe et al, 2007). Moreover, we explored the anti-proliferative activity of CIU1 on the EGFR-low liver cancer cell line and the EGFR-high colorectal cell line HepG2 (Itabashi et al, 2008) and HT29 (Matsuo et al, 2011), respectively. The number of viable cancer cells after 24 h treatment of CIU1 was evaluated using the WST-1 (a water-soluble tetrazolium salt, (2-(4-iodophenyl)-3-(4-nitrophenyl)-5-(2,4-disulfophenyl)-2H-tetrazolium monosodium salt) colorimetric assay.…”
Section: Sensitivity Over a Panel Of Solid Tumor Cell Linesmentioning
confidence: 98%
“…60 ADAM17 also influences tumour cell proliferation when over-expressed in cancers such as breast, 61 ovary, 62 kidney, 63 colon, 64 prostate 65 and primary hepatocellular carcinomas. 66 A mechanism proposed by Itabashi et al 66 suggested that this increased cellular proliferation is mediated by ADAM proteins, particularly ADAM17, via EGFR signal transactivation triggered by angiotensin II (Ang II) stimulation. The direct stimulation of EGFR by ligand binding results in the dimerisation and subsequent phosphorylation of the two receptor molecules.…”
Section: Adams and Cancermentioning
confidence: 99%
“…67 Ang II acts as a potent growth factor of vascular smooth muscle cells and certain cancer cell lines in addition to its fundamental role as a vasoconstrictor controlling cardiovascular function and renal homeostasis. 66 Similarly, amphiregulin (a ligand of EGFR) is released by ADAM17 68 and enhances proliferation of cancer cells. 20…”
Section: Adams and Cancermentioning
confidence: 99%